Ozone reaction kinetics for water and wastewater systems. - Beltran, Fernando J., ....- (Boca Raton : CRC, 2004)
Interest in ozonation for drinking water and wastewater treatment has soared in recent years due to ozone's potency as a disinfectant, and the increasing need to control disinfection byproducts that arise from the chlorination of water and wastewater. Ozone Reaction Kinetics for Water and Wastewater Systems is a comprehensive reference that presents practical information to water treatment and wastewater treatment operators and researchers. It describes the application of kinetics to the effective evaluation, design, and implementation of ozone technology. This information will help plant operators determine whether or not ozone treatment is suitable for their facility, and help engineers and researchers design appropriate ozone treatment systems. By presenting complete coverage of ozone kinetics in water and wastewater, this book provides researchers and practitioners with fundamentals of ozone kinetics as well as practical "how to" information.
Keywords: Afvalwater; Waterzuivering